Analisis Tindakan Sosial Max Weber Terhadap Tradisi Siraman Sedudo - Fathiha, Aprillia Reza (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2022)
The Siraman Sedudo tradition is a tradition that has existed since ancient times, which is carried out from generation to generation once a year in the month of Suro. This study aims to examine the portrait of the Siraman Sedudo tradition and analyze this tradition from the perspective of Max Weber’s social action theory. The method used is a qualitative research method. Collecting data through observation, interviews, and documentation. Sources of data obtained from informants who are directly involved with implementing the Siraman Sedudo tradition, documentation from books and scientific journals that support research. This research focuses on implementing the Siraman Sedudo ritual for the local community in Ngliman Village, Sawahan District, Nganjuk Regency, which is basically the goal and what they want to achieve from following the siraman tradition is analyzed using four kinds of social action theory from Max Weber, namely: action traditional, value-oriented action, goal-oriented action, and affective action. This study found that in carrying out the siraman ritual it has a meaning that is expected to bring blessings to an individual who takes part in the ritual's implementation. From the findings of this study, it is hoped that the community can preserve their traditions to maintain the diversity that exists in Indonesia.